An integrated approach to sustainable development, National Resilience, and COVID-19 responses: The case of Japan (2020)
The COVID-19 pandemic has led to historic economic fallout. To protect public health and stabilize incomes, governments have implemented massive fiscal stimulus packages. These fiscal supports are crucial, though there is concern that sustainable and resilient development will be sacrificed in the rush to preserve incomes and industries. The aim of the paper is to review whether the Japanese governments’ responses in terms of financial stimulus considers longer term resilience and sustainability. This paper reviews pertinent academic literature and publicly available data from governments and organisations. The research is a rapid analysis of emerging information provided by the government of Japan and other international organisations. Using the case of Japan, this paper suggests that it is possible both to protect public health and essential services, while also promoting resilience and sustainability. Japan’s integrated solutions show that pandemic response can include accelerated decarbonization and resilient, sustainable development. The paper also warns also that failure to act on longterm sustainability risks increased inequality, higher opportunity costs, cascading hazards, and further retreat from planetary thinking and globalism.